القياس المحاسبي للأصول غير الملموسة وفق المعيار المحاسبي الدولي /38/ دراسة مقارنة مع النظام المحاسبي الأساسي لعام 2007 - رزوق, ساطع; عزيز, عزو (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تناول هذا البحث موضوع الأصول غير الملموسة كأحد أهم الأصول في شركات الأعمال، والتي برزت أهميتها مع التحول إلى اقتصاديات المعرفة التي يتزايد فيها الاستثمار في هذا النوع من الأصول بشكل واضح. وتم التطرق من خلال البحث إلى مفهوم ومكونات الأصول غير الملموسة، ومتطلبات القياس المحاسبي عنها وفق المعيار المحاسبي الدولي/38/، ومقارنة هذه المتطلبات مع ما جاء به النظام المحاسبي الأساسي في هذا المجال. تم من خلال الدراسة التطبيقية توزيع استبيان على عينة من العاملين في المجال المحاسبي، وتضمن الاستبيان مجموعة من الأسئلة التي تبين متطلبات القياس المحاسبي للأصول غير الملموسة وفق المعيار /38/، ومن خلال الإجابات تم تحديد مدى التزام النظام المحاسبي بمتطلبات القياس التي جاء بها المعيار المحاسبي الدولي المذكور. وتوصل الباحث إلى نتيجة مفادها تدني نسبة التزام النظام المحاسبي الأساسي بمتطلبات المعيار المحاسبي الدولي/38/ فيما يخص متطلبات القياس المحاسبي للأصول غير الملموسة، وأوصى الباحث بضرورة زيادة استثمار الشركات في هذه الأصول نظراً لارتفاع العائد من عملية الاستثمار فيها،وهذا سيشكل دافعاً للنظام المحاسبي لتناول موضوع الأصول غير الملموسة بشكل أوسع، ومواجهة أي مشاكل محاسبية تتعلق بعملية القياس والإفصاح عن المعلومات الخاصة بها مستقبلاً وفق ما جاء به معيار المحاسبة الدولي /38/. This search discussed subject of intangible assets as one of the most important assets in the assessment of businesses which its importance appeared with the transference to economies of learning that the development increases in this quality of assets clearly. The task is performed by the research to highlight the meaning and components of intangible assessment and the requirements of the measurement accounting according to the international accounting standard /38/ and comparing these requirements with what is mentioned in the basic accounting system in this domain. By this field study, we issued an application model on a number of workers in the accounting domain, and this model included a collection of questions that show the requirements of the accounting measurement for the intangible assets according to the system /38/. And through the answers, we could determine the degree of the accounting system commitment to the measurement requirements that are mentioned in the above-mentioned international system. The study reached this result: the decline of the commitment level of the basic accounting measurement to the requirements of the international accounting system 38 that is concerned with the acquiring system requirements of intangible assets. This research recommended the necessity of increasing the investment of the companies that are involved in these mentioned assets because of increasing the outcome of this investment. This will motivate the accounting system to tackle the issue of intangible assets more widely, and this will lead to face any accounting problems related to the measurement process, and mention any special information about this issue in the futire according to what is mentioned in the international accounting Standard /38/.